PERBAIKAN PETA SIGPBB DENGAN MEMANFAATKAN MOSAIK TERKONTROL FOTO UDARA FORMAT KECIL DIGITAL - Mokh.Solikhun
Abstracts: This research was based upon the preliminary facts found from the field regarding the existence of differences in the extend of land area measurement to SISMIOP attribute with data measurement of area width as a result of plotting the SIGPBB map at the PBB Tax Office of Serang Regency. Research conducted by comparing the land width between attribute data of SISMIOP with the measurement of the extension resulting from plotting the SIGPBB map and testing the difference wideness by means to test the correctness tolerance condition according to Kep-DJP No.533/PJ./2000. The outcome from evaluating 113 tax parcels was that only 28% were up to the standard tolerance. Thus, most of the data on the wideness of land area at block 009 results from plotting the SIGPBB map have differences exceeding 10% so that it did not comply with the criterions, which have been specified in the PBB. Hereinafter the research was directed by means of using Small Format Aerial Photograph Controlled Mosaic (MTFUFKD). MTFUFKD was identified, delineated, and digitized interpretated objects visually. The result base on the conducted analysis, it is recognize that out come of digitation of MTFUFKD map plotting at block 009 accumulatively can be accepted because average differences of spatial width was less than 10% (3,84%). While difference wideness of every land area shown 99.12% fullfiled to Kep-533/PJ/2000, and 0.88% ineligible. Thereby, MTFUFKD can be utilized for updating the SIGPBB map for block 009 Kota Baru village.